y = (13 - 3x)/2 and that cannot be simplified further.
3x + 2y = 13Subtract 3x from each side:2y = -3x + 13Divide each side by 2:y = (-3/2)x + (13/2)The graph is a straight line, with a slope of (-3/2),through the point (0, 13/2) .
3x+5y+8x+2y combine 3x and 8x to get 11x 11x+5y+2y combine 5y and 2y 11x+7y is the answer.
3x + 2y = 7
-5(x + 2y) -3x + 8y + 5 = -5x -10y -3x + 8y + 5 = -8x -2y + 5
4x-2y+3x+2y When simplified: 7x
y = (13 - 3x)/2 and that cannot be simplified further.
56xy + 2y + 3x
-3x + 2y = 9 2y = 3x + 9y = 1,5x + 4,5
3x + 2y = 13Subtract 3x from each side:2y = -3x + 13Divide each side by 2:y = (-3/2)x + (13/2)The graph is a straight line, with a slope of (-3/2),through the point (0, 13/2) .
3x+5y+8x+2y combine 3x and 8x to get 11x 11x+5y+2y combine 5y and 2y 11x+7y is the answer.
3x - 2y + 7x + 4y = 3x + 7x - 2y +4y = (3+7)x + (-2+4)y = 10x + 2y
3x + 2y = 7
The equation can be simplified to show a value of Y in terms of X. 3X + 2Y +2 = 4Y + 4 3X + 2 = 2Y + 4 3X -2 = 2Y and 2Y = 3X - 2 means that Y = (3/2 X) -1
3x + 2y + 5 - 3 = 3x + 2y + 2 No further simplification is possible. This is an expression, not an equation so there cannot be a solution.
-5(x + 2y) -3x + 8y + 5 = -5x -10y -3x + 8y + 5 = -8x -2y + 5
3x = 2y + 3 3x -3 = 2y +3 -3 3x - 3 = 2y (3x -3)/2 = 2y / 2 y = 1/2 x (3x - 3) 3x = 2y +3 3x - 3x = -3x +2y +3 0 = -3x +2y +3 -1 x (0) = -1 x (-3x +2y +3) 0 = 3x - 2y -3